Supplemental Effects of Phytase on Modulation of Mucosa-Associated Microbiota in the Jejunum and the Impacts on Nutrient Digestibility, Intestinal Morphology, and Bone Parameters in Broiler Chickens - Vitor Hugo C. Moita; Marcos Elias Duarte; Sung Woo Kim (Animals, 2021)
This study aimed to determine supplemental effects of phytase on modulation of the mucosa-associated microbiota in the jejunum, intestinal morphology, nutrient digestibility, bone parameters, and growth performance of broiler chickens. Three hundred and sixty newly hatched broiler chickens (Ross 308) (44 ± 2 g BW) were randomly allotted in 6 treatments with 10 birds per cage based on a completely randomized design and fed for 27 d. The treatments consisted of one negative control (NC), diet formulated meeting the requirements suggested by Ross recommendations (2019), and without phytase supplementation. The other treatments consisted of a positive control diet (PC) formulated with 0.15% deficient Ca and P and split into 5 treatments with different phytase inclusion levels (0, 500, 1000, 2000, 4000 FTU/kg feed). Titanium dioxide (0.4%) was added to feeds as an indigestible marker to measure apparent ileal digestibility (AID) of nutrients. On d 27, 3 birds were randomly selected from each cage and euthanized to collect samples for analyzing the mucosa-associated microbiota in the jejunum, oxidative stress status, AID, and bone parameters. Data were analyzed using the proc Mixed of SAS 9.4. Phytase supplementation tended to have a quadratic effect (p = 0.078) on the overall ADG (maximum: 41 g/d at 2833 FTU/kg of feed). Supplementation of phytase at 2,000 FTU/kg increased (p < 0.05) the relative abundance of Lactobacillus and reduced (p < 0.05) Pelomonas. Moreover, it tended to reduce Helicobacter (p = 0.085), Pseudomonas (p = 0.090) Sphingomonas (p = 0.071). Phytase supplementation increased (p < 0.05) the villus height and the AID of CP; and tended to increase (p = 0.086) the AID of P. Phytase supplementation increased (p < 0.05) breaking strength and P content in the tibia. In conclusion, phytase supplementation showed potential benefits on the modulation of the mucosa-associated microbiota in the jejunum by tending to reduce harmful bacteria (Pelomonas, Helicobacter, and Pseudomonas) and increase beneficial bacteria (Lactobacillus). In addition, it showed positive effects increasing apparent ileal digestibility of CP and P, enhancing intestinal morphology (villus height), and improving the bone parameters (bone breaking strength, ash, and P content). Phytase supplementation at a range of 38 to 59 FTU/d or 600 to 950 FTU/kg of feed provided the most benefits related to nutrient digestibility.